Zika virus infection drives epigenetic modulation of immunity by the histone acetyltransferase CBP of Aedes aegypti. - Anderson de Mendonça Amarante; Isabel Caetano de Abreu da Silva; Vitor Coutinho Carneiro; Amanda Roberta Revoredo Vicentino; Marcia de Amorim Pinto; Luiza Mendonça Higa; Kanhu Charan Moharana; Octavio A C Talyuli; Thiago Motta Venancio; Pedro Lagerblad de Oliveira; Marcelo Rosado Fantappié (Public Library of Science (PLoS), 2022)
Epigenetic mechanisms are responsible for a wide range of biological phenomena in insects, controlling embryonic development, growth, aging and nutrition. Despite this, the role of epigenetics in shaping insect-pathogen interactions has received little attention. Gene expression in eukaryotes is regulated by histone acetylation/deacetylation, an epigenetic process mediated by histone acetyltransferases (HATs) and histone deacetylases (HDACs). In this study, we explored the role of the Aedes aegypti histone acetyltransferase CBP (AaCBP) after infection with Zika virus (ZIKV), focusing on the two main immune tissues, the midgut and fat body. We showed that the expression and activity of AaCBP could be positively modulated by blood meal and ZIKV infection. Nevertheless, Zika-infected mosquitoes that were silenced for AaCBP revealed a significant reduction in the acetylation of H3K27 (CBP target marker), followed by downmodulation of the expression of immune genes, higher titers of ZIKV and lower survival rates. Importantly, in Zika-infected mosquitoes that were treated with sodium butyrate, a histone deacetylase inhibitor, their capacity to fight virus infection was rescued. Our data point to a direct correlation among histone hyperacetylation by AaCBP, upregulation of antimicrobial peptide genes and increased survival of Zika-infected-A. aegypti.